Efektivitas Metode Praktikum Indikator asam Basa Berbasis Contextual Teaching Learning ( CTL ) terhadap Hasil Belajar Siswa Kelas XI SMA Negeri 7 Pontianak - Hary saputra; Tuti Kurniati; Raudhatul Fadhilah (Jurnal Ilmiah Ar-Razi, 2020)
This research is motivated by the low learning outcomes of students of class XI IPA of SMA Negeri 7 Pontianak in learning chemistry, especially indicator theory sub material. This study aims to determine the learning outcomes between students who are taught using the Acid Base Indicator Practicum Method Based on Contextual Teaching Learning (CTL) and students who are taught with the Discovery Learning model based on practicum. This study uses Intact Group Comparison Design with research subjects of 15 control class students and 16 experimental class students. Data were collected using direct communication techniques: interview sheets, measurement techniques, and direct observation techniques, observation sheets and data collection tools using learning outcomes tests (pretest and posttest). The results of the average pretest and posttest of the control class were 35.1 and 66.1 respectively, the average pretest and posttest of the experimental class were 36.9 and 74.5. Learning outcomes data using the Mann Whitney U-test obtained learning outcomes with a probability number, i.e. P value (0.644)> α (0.05). This means that there are differences in student learning outcomes between the control class and the experimental class. Thus the acid-base indicator practicum method (CTL) gives the Effect Size obtained a value of 0.78 effectiveness of 75.80%. This means that there are differences in student learning outcomes between the control class and the experimental class. Thus the acid-base indicator practicum method (CTL) gives the Effect Size obtained a value of 0.78 effectiveness of 75.80%. This means that there are differences in student learning outcomes between the control class and the experimental class. Thus the acid-base indicator practicum method (CTL) gives the Effect Size obtained a value of 0.78 effectiveness of 75.80%.